Investigation of Commiphora myrrha (Nees) Engl. Oil and Its Main Components for Antiviral Activity - Valentina Noemi Madia; Marta De Angelis; Daniela De Vita; Antonella Messore; Alessandro De Leo; Davide Ialongo; Valeria Tudino; Francesco Saccoliti; Giovanna De Chiara; Stefania Garzoli; Luigi Scipione; Anna Teresa Palamara; et al. (MDPI AG, 2021)
The resinous exudate produced by Commiphora myrrha (Nees) Engl. is commonly known as true myrrh and has been used since antiquity for several medicinal applications. Hundreds of metabolites have been identified in the volatile component of myrrh so far, mainly sesquiterpenes. Although several efforts have been devoted to identifying these sesquiterpenes, the phytochemical analyses have been performed by gas-chromatography/mass spectrometry (GC-MS) where the high temperature employed can promote degradation of the components. In this work, we report the extraction of C. myrrha by supercritical CO2, an extraction method known for the mild extraction conditions that allow avoiding undesired chemical reactions during the process. In addition, the analyses of myrrh oil and of its metabolites were performed by HPLC and GC-MS. Moreover, we evaluated the antiviral activity against influenza A virus of the myrrh extracts, that was possible to appreciate after the addition of vitamin E acetate (α-tocopheryl acetate) to the extract. Further, the single main bioactive components of the oil of C. myrrha commercially available were tested. Interestingly, we found that both furanodienone and curzerene affect viral replication by acting on different steps of the virus life cycle.